Letter - Bowen, J. W.
001-0051-001 INTERNATIONALE DES PERSONALS DER POST-. TELEGRAPHEN - UND TELEPHON-BETRIEBE INTERNATIONALE DU PERSONNEL DES POSTES, TELEGRAPHES ET TELEPHONES POSTAL, TELEGRAPH AND TELEPHONE INTERNATIONAL Secretary: FRITZ GMUR, 100. LIEBEFELDSTRASSE. LIEBEFELD, NR. BERN. SWITZERLAND President: J. W. BOWEN. 18 TITCHWELL ROAD, WANDSWORTH COMMON LONDON. S.W.18. Ref. No. Oct. 26th 1945 Mr J. Bell Trade Union Congress Dear Mr Bell, Reference to our 'phone conversation this morning. Last night I received a telegram from our International Secretary as follows - " Please try by T.U.C. or British Diplomacy urge Spanish Government to save life of condemned telegraphist Ricardo [Escrig ?] Gonzalvo leading member of resistance. Gunnar It is rather vague but if you can possibly make any direct or indirect representations, all our people would be very grateful. Yours sincerely J. W. Bowen. 292/946/1/51